Nick & Norah's infinite playlist - Kohansky, Kerry; Miano, Andrew; Weitz, Chris, 1969-; Weitz, Paul, 1966-; Scafaria, Lorene; Sollett, Peter, 1976-; Cera, Michael; Dennings, Kat, 1986-; Yoo, Aaron, 1979-; Gavron, Rafi.; Graynor, Ari.; Dziena, Alexis, 1984-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2009)
Nick knows exactly how long it has been since Tris broke up with him - three weeks, two days, and 23 hours. Now she is at his gig, with a new guy. Nick can't understand how she could have moved on so fast. But that night, Nick meets Norah. They have nothing in common except their taste in music. This begins the night of Nick, Norah and Manhattan. Now, this chance meeting will turn into a crusade to find a legendary rock band's secret show, ends up being a first date and a night that will change their lives forever.
English track: Dolby digital 5.1.
French track: Dolby digital surround.
Title from container.
Based on the novel by Rachel Cohn & David Levithan.
Originally released as a motion picture in 2008.
Special features: Digital copy of the film; outtakes; deleted scenes; 'Middle management' music video by Bishop Allen; a Nick & Norah puppet show by Kat Dennings; filmaker & cast commentaries.
Keywords: Musicians -- New York (State) -- New York -- Drama; Rock concerts -- New York (State) -- New York -- Drama; Dating (Social customs) -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama; Romantic comedy films; Musical films; Feature films; Films for the hearing impaired